Being the Winner Is Being the Loser When Playing a Parental Tug-of-War – A New Framework on Stability of Biparental Care - Wojczulanis-Jakubas, Katarzyna (Frontiers in Ecology and Evolution, 2021)
Because there are basic sexual differences in reproductive potential, and the cost of parental care is assumed to be high, biparental care is viewed as a constant tug-of-war between the partners. This raises the question of the system’s evolutionary stability. Several models have been proposed to resolve this problem but none has received unequivocal support. Here, I propose a framework that not only integrates the earlier theoretical ideas (sealed bids, negotiation) but also considers the importance of the environment (frequently neglected in previous models) and views the cost of parental care from a different perspective (costly in terms of parent’s survival only when performed close to the boundary of parental capacity). The framework suggests that sexual conflict may not be such a significant factor mediating parental care as commonly assumed, and that a parent trying to shift the parental burden onto the partner - assumed to be the winner in the tug-of-war interplay - is actually more likely to be a loser, as doing so may put the success of the current breeding attempt in jeopardy, thereby reducing overall fitness of the parent. Once it is realized that the importance of sexual conflict is actually much less than it seems, it becomes clear that the stability of the biparental care system no longer seems to be such a puzzling issue.